Moving beyond quality control in diagnostic radiology and the role of the clinically qualified medical physicist. (September 2017) - Delis, H.; Christaki, K.; Healy, B.; Loreti, G.; Poli, G.L.; Toroi, P.; Meghzifene, A.
Highlights: The concept of QC in diagnostic radiology has to be replaced by a more comprehensive framework of quality. Clinically qualified medical physicists are required to support this framework of quality. Proper evaluation and quantification processes are required to demonstrate quality in diagnostic radiology. Comprehensive clinical audit processes should be an inherent component in any quality system. Abstract: Quality control (QC), according to ISO definitions, represents the most basic level of quality. It is considered to be the snapshot of the performance or the characteristics of a product or service, in order to verify that it complies with the requirements. Although it is usually believed that "the role of medical physicists in Diagnostic Radiology is QC", this, not only limits the contribution of medical physicists, but is also no longer adequate to meet the needs of Diagnostic Radiology in terms of Quality. In order to assure quality practices more organized activities and efforts are required in the modern era of diagnostic radiology. The complete system of QC is just one element of a comprehensive quality assurance (QA) program that aims at ensuring that the requirements of quality of a product or service will consistently be fulfilled. A comprehensive Quality system, starts even before the procurement of any equipment, as the need analysis and the development of specifications are important components under the QA framework. Further expanding this framework of QA, a comprehensive Quality Management System can provide additional benefits to a Diagnostic Radiology service. Harmonized policies and procedures and elements such as mission statement or job descriptions can provide clarity and consistency in the services provided, enhancing the outcome and representing a solid platform for quality improvement. The International Atomic Energy Agency (IAEA) promotes this comprehensive quality approach in diagnostic imaging and especially supports the field of comprehensive clinical audits as a tool for quality improvement.